ENVIRONMENTAL AND ECONOMIC JUSTIFICATION OF IMPLEMENTATION TECHNOLOGY FOR PRODUCING BIOGAS FROM WASTE - Дичко, Аліна Олегівна; Ополінський, Ігор Олегович (Science-based technologies, 2016)
The benefits of technologies of anaerobic waste and wastewater treatment include: possibility to have additional source of energy, electric power and heat output, producing of fertilizers from active sludge, decrease of areas of treatment equipment, elimination of methane emission into atmosphere. The aim of research is to develop the methodology of grounding and calculating of ecologic and economic effectiveness of implementation of technology of waste and wastewater anaerobic treatment with biogas output. Practical value of research is elaboration of the universal method to determine the environmental and economic assessment of implementation of technology of anaerobic digestion of waste with biogas output. Originality of the research is that developed methodology includes benefits from increased biogas producing due to methods of intensification of waste biotransformation. It is analyzed the feasibility of implementing of biogas equipment for enterprise with productivity of formation of organic waste in the amount of 60 tons/day. Thus, use of anaerobic technology of organic waste utilization with intensification of the methanogenesis increases biogas productivity in 4 times and decreases period of plant payback to 9 months. It is determined that amount of the annual production of biogas suitable for sale is 2.7 million m3. Reduction of annual environmental charges for waste disposal is 2.9 million of UAH. The size of annual economic effect of implementation of biogas technologies is 2.59 million of UAH, and with use of process intensification – is 45.87 million of UAH. The payback period is 2 years and 8 months. Use of the technology of process intensification allows reducing the payback period to 9 months. The research of detailed assessment of new technologies of biogas output from different biomass or wastewaters, taking into account local conditions, ecological norms and “green” tariffs for bioenergy will be perspective.